PENGARUH STRUKTUR DEWAN DIREKSI TERHADAP PENGUNGKAPAN LAPORAN KEBERLANJUTAN PERUSAHAAN - Patrick Justin; Paulus Th Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2019)
This study aims to examine the effect of board size, board with female directors, and board ownership as an independent variable to firm’s sustainability reporting as a dependent variable. The population in this study is 100 companies in Indonesia that are listed on Bursa Efek Indonesia in the year 2014-2017. The method used for sampling is proportional stratified sampling. Yielding a final sample of 400 firm-year observations. This study used logistic regression to examine the hypothesis. The result of this study shows that board size positively affecting firm’s sustainability reporting. Board with female directors shows a negative effect to firm’s sustainability reporting. While, board ownership does not show any significant effect to firm’s sustainability reporting.